Modern management technologies - Ilchenko, Svitlana; Kostiuk, Yurii; Cherchуk, Larysa; Khumarova, Nina; Tsymbaliuk, Iryna; Pavlikha, Nataliia; Voichuk, Maksym; Shubalyi, Oleksandr; Volynets, Iryna; Bortnik, Svitlana; Yushchyshyna, Larysa; Mylko, Inna; et al. (Higher School of Social and Economic. Przeworsk, 2022)
The analysis of modern management concepts indicates the need to implement approaches and principles ensuring the integrity of the research object as the social, ecological, and economic system, which is a separate enterprise or region. Such approach allow to consider issues as complex at each level and identifying risks, making forecasts regarding changes in the environment, evaluating opportunities for development and ensuring an acceptable life quality for people, the human development level in terms of natural resource and environmental limitations and other local and global challenges. Currently, the need to accumulate human intellectual efforts is becoming more and more obvious. It forms a new paradigm of its existence in the conditions of non-antagonistic self-development and coexistence with the surrounding world, economic interests’ subordination to interests of ecological expediency and social responsibility. Therefore, it is necessary to form a new management paradigm with worldview level emphasis and basic values that combine environmental, economic, social, and political aspects. This monograph based on the authors research results, which developing the ideas of the sustainable development transition necessary, and basics of a green economy and a socially oriented market economy. The presented materials have both applied (theoretical and methodological) and didactic value, as they demonstrate the implementation conditions and features of effective management’s tools and methods to solve urgent development problems of enterprises, activity spheres and territories. Therefore, it will be essential and useful for enterprises’ managers, local self-government bodies, scientists and university students.
Keywords: Sustainability management; Management of spheres and types of activities; Management of organizations